Investigation of Panic Attack Patients Who Applied with Chest Pain to Bezmialem Vakif University Emergency Department - Dogan, Ahmet Burhan; Taşlıdere, Bahadır; TAŞLIDERE, BAHADIR (My University, 2021)
Introduction: Panic attacks are severe attacks of fear and anxiety that occur at certain times. Chest pain is a common symptom of panic attacks. Especially the presence of chest pain causes repetitive emergency department admissions. We aimed to prevent the inappropriate treatment given to these patients by investigating the panic attack patients for whom the diagnosis of Acute Coronary Syndrome was ruled out. Method: This study was carried out retrospectively. We evaluated the patients who presented to the emergency department of Bezmialem Vakif University with chest pain and panic attack symptoms. Patients diagnosed with Panic Attack in the Emergency Service between May 1, 2020 and October 31, 2020 were included in the study. Results: In this study, 32 patients with chest pain among 136 patients diagnosed with panic attack were included. According to our hospital-s database, it was seen that the average number of attacks experienced by patients in a week was 1.25. Therefore, 37.5% of the patients applied more than once. Echocardiography or ultrasonography was requested for a total of 17 people (53.1%). In addition, tomography or magnetic resonance imaging was performed in 14 patients (43.8%). The analysis and imaging results requested from the patients were normal. Most of the patients who presented to the emergency department with chest pain complaints were discharged after excluding life-threatening conditions. In addition, they were referred to the psychiatry service. Conclusion: A panic attack should be considered after it is confirmed by physical examination and various tests that the pain is not caused by cardiac reasons. The problem should be explained to the patient who has applied with chest pain to the emergency department and diagnosed with a panic attack. Then, the patient should be referred to the psychiatry department. In case of repeated admissions to the emergency department with atypical chest pain, we should definitely consider panic attacks. Thus, unnecessary medical analysis, polypharmacy and use of unnecessary drugs by patients are avoided. Key words: Panic attack, chest pain, emergency service